Toxoplasma gondii: Entry, association, and physiological influence on the central nervous system. - Oscar A Mendez; Anita A Koshy (PLoS Pathogens, 2017)
Toxoplasma gondii is one of the world's most successful parasites, in part because of its ability to infect and persist in most warm-blooded animals. A unique characteristic of T. gondii is its ability to persist in the central nervous system (CNS) of a variety of hosts, including humans and rodents. How, what, and why T. gondii encysts in the CNS has been the topic of study for decades. In this review, we will discuss recent work on how T. gondii is able to traverse the unique barrier surrounding the CNS, what cells of the CNS play host to T. gondii, and finally, how T. gondii infection may influence global and cellular physiology of the CNS.